Effect of Financial Performance and Capital Structure on Company Value in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2017-2021 - Dodi Suryadi (Journal of Applied Management and Business Administration, 2023)
The purpose of this research is to look at the effect of financial performance and capital structure on industry value. This research design uses a descriptive research design. The population used in this research is the Manufacturing Industry listed on the Indonesia Impact Exchange (IDX). The research observation period was tried from 2017-2021. The illustrations used in this research are as many as 63 industries in the manufacturing industry listed on the Indonesia Stock Exchange. There is also a method of selecting illustrations in this research using the purposive sampling method with the aim of obtaining a representative illustration according to the criteria that have been set. The analysis method in this study uses multiple linear regression analysis procedures The test equipment used in this research was using the IBM SPSS Statistics type 25 application. Based on analysis and reviews, financial performance partially affects the value of the industry significantly with a significant value of 0.000. The capital structure partially does not affect the value of the industry with a significant value of 0.721. Financial performance and capital structure together have a significant effect on the value of the industry with a significant value of 0.000.